The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fnhum.2019.00017
|View full text |Cite|
|
Sign up to set email alerts
|

The Importance of the Validation of M/EEG With Current Biomarkers in Alzheimer's Disease

Abstract: Current biomarkers used in research and in clinical practice in Alzheimer's Disease (AD) are the analysis of cerebral spinal fluid (CSF) to detect levels of Aβ42 and phosphorylated-tau, amyloid and FDG-PET, and MRI volumetry. Some of these procedures are still invasive for patients or expensive. Electroencephalography (EEG) and Magnetoencephalography (MEG) are two non-invasive techniques able to detect the early synaptic dysfunction and track the course of the disease. However, in spite of its added value they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 83 publications
9
56
0
Order By: Relevance
“…In AD demented patients, the neurodegeneration is in a more advanced stage and it would be expected that the EEG recordings would be affected. Unfortunately, the common issue with studies in the dementia stage of AD is either a lack of amyloid or tau biomarkers, the absence of longitudinal data, and small investigated populations 34 . Longitudinal studies without biomarker confirmation have shown that, in line with our results, more severe EEG abnormalities correlate with a faster cognitive decline.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In AD demented patients, the neurodegeneration is in a more advanced stage and it would be expected that the EEG recordings would be affected. Unfortunately, the common issue with studies in the dementia stage of AD is either a lack of amyloid or tau biomarkers, the absence of longitudinal data, and small investigated populations 34 . Longitudinal studies without biomarker confirmation have shown that, in line with our results, more severe EEG abnormalities correlate with a faster cognitive decline.…”
Section: Discussionsupporting
confidence: 83%
“…The relation between CSF tau and EEG is difficult as these markers seem to develop differently over time. As literature is sparse, future studies should investigate the cross‐sectional and longitudinal correlations between EEG and CSF AD markers 34 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the clinical application of in vivo biomarkers for amyloid and tau pathology (eg, positron emission tomography and cerebrospinal fluid analysis) has attracted attention in recent years. However, general clinical use of these tests is difficult due to problems such as their invasiveness and cost 3 . For these reasons, there is an urgent need to develop non‐invasive, easy to perform, and low‐cost biomarkers for early diagnosis of MCI.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible explanation would concur with the results obtained in other neurodegenerative diseases such as Alzheimer's; Lopez et al [65] found increased functional brain activity in anterior circuits using magnetoencephalography in mild cognitive impairment (an early condition in dementia). In [66], it was suggested that this hyperactivity may be one of the earliest dysfunctions of the pathophysiological process of neurodegeneration and would subsequently decline as dementia develops [67].…”
Section: Discussionmentioning
confidence: 99%